A SYSTEMATIC LITERATURE REVIEW ON RISK IDENTIFICATION TOWARDS A PUBLIC-PRIVATE PARTNERSHIP APPROACH IN BUILDING REUSE PROJECTS - Mohd Zaki, Erni Farmiza; Jaafar, Mastura; Syed Abu Bakar, Syed Putra; Mohd Raslim, Faraziera (International Journal of Property Sciences (E-ISSN: 2229-8568), 2023)
This paper aims to systematically review a wide range of literature to provide insights on the risk of public-private partnership (PPP) projects. The authors have critically reviewed the risk elements from the entire spectrum of the construction industry. Thus, the systematic literature review (SLR) method was employed to synthesise research with precise attention to detail. To achieve research objectives and to retrieve articles related to PPP and risk identification building adaptive reuse, the following database was utilised: Scopus, Google Scholar, ScienceDirect, and Web of Science. Number of related themes were collected and analysed according to the coding structure. The results present that a total of twelve (12) risk categories have been identified from the existing literature, namely, political, economic, legal, natural, demand risk, financial, residual asset risk, design, construction, operation, partner selection, and contract risk, respectively. These categories were further divided into fifty-seven (57) different risk factors, whereby the classifications were perceived to be related to the PPP project. In addition, sixteen (16) risk factors were identified in the context of building adaptive reuse specifically, focusing on feasibility and procurement stages. Consequently, the present review recognised the knowledge gaps to offer a new perspective on risk identifications in the context of building adaptive reuse in Malaysia.